Reliability of the Behaviorally Anchored Rating Scale (BARS) for assessing non-technical skills of medical students in simulated scenarios - Jaycelyn R Holland; Donald H Arnold; Holly R Hanson; Barbara J Solomon; Nicholas E Jones; Tucker W Anderson; Wu Gong; Christopher J Lindsell; Travis W Crook; Daisy A Ciener (Medical Education Online, 2022)
Purpose Caring for critically ill patients requires non-technical skills such as teamwork, communication, and task management. The Behaviorally Anchored Rating Scale (BARS) is a brief tool used to assess non-technical skills. The investigators determined inter- and intra-rater reliability of the BARS when used to assess medical students in simulated scenarios.Method The investigators created simulation scenarios for medical students during their pediatric clerkship. Content experts reviewed video recordings of the simulations and assigned BARS scores for four performance components (Situational Awareness, Decision-Making, Communication, and Teamwork) for the leader and for the team as a whole. Krippendorff’s alpha with ordinal difference was calculated to measure inter- and intra-rater reliability.Results Thirty medical students had recordings available for review. Inter- and intra-rater reliability for performance components were, respectively, Individual Situational Awareness (0.488, 0.638), Individual Decision-Making (0.529, 0.691), Individual Communication (0.347, 0.473), Individual Teamwork (0.414, 0.466), Team Situational Awareness (0.450, 0.593), Team Decision Making (0.423, 0.703), Team Communication (0.256, 0.517), and Team Teamwork (0.415, 0.490).Conclusions The BARS demonstrated limited reliability when assessing medical students during their pediatric clerkship. Given the unique needs of this population, a modified or new objective scoring system for assessing non-technical skills may be needed for medical students.